ENHANCING THE EFFICIENCY OF THE CIVIL SERVICE IS A GUARANTEE OF ADMINISTRATIVE REFORMS - Yusubov Jamshid Qadamovich (Journal Park Publishing, 2025)
The article discusses the importance of administrative reforms in increasing the efficiency of the state civil service in Uzbekistan and provides opinions on this issue. At the same time, analytical data on the issue of personnel in accelerating the development of our country are presented.
Keywords: Administrative reform, state civil service, personnel policy,public administration, head, control system.